IMU-based field diagnosis for jumping and sprinting in track and field events - Schmidt, M.; Rheinlaender, C.; Wille, S.; Jaitner, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In highly dynamical sports, such as track and field, athletes must be able to generate high forces within a very short time. Temporal parameters like stance and flight durations during jumping and sprinting represent main indicators of performance (Slawinski et al., 2010). Objective feedback of these parameters is crucial to ensure a high quality of training as sprinting and jumping performance cannot be assessed precisely enough by pure observation or over longer distances. In this study, we present an IMU-based wearable measurement system for field-based performance analysis and online monitoring for a group of athletes, that allows an accurate in-field detection of temporal parameters in track and field events. Methods: For the group monitoring of stance durations (tS) in field-based conditions a wearable measurement system including inertial sensors (IMU), a microcontroller unit, a detection algorithm and an Android ™ application was developed. Evaluation studies included 18 participants for Dropjumps (DJ) as well as 12 participants for sprints (SP). Reference measures were a force plate, a contact mat and the Optojump™ system (OJ), respectively . For statistical analyses, absolute differences and Bland-Altman-Plots (BAP) of tS between IMU and reference measurements were calculated. Results: Throughout the DJ protocol participants executed an overall of 204 jumps including 194 correct detections (95%). Mean absolute difference for tS was 4.7±3.5ms and BAP 95% limits of agreement (LoA) ranges from 13 to -7.3ms. Out of 380 contacts during sprinting, 364 were detected correctly (96%). tS showed a mean absolute difference of 4.3±3.2ms between OJ and IMU. BAP derive LoA in the range from 6.8 to -11.8 ms. Discussion: The IMU device provides reliable and accurate measurements of stance and flight durations and can be considered as a suitable tool for jump and sprint diagnostics. The accuracy of the system is higher compared to previous studies (e.g. Bergamini et. al,2012). Overall, the system enables providing objective real-time feedback for a group of athletes during a training session or competition and can overcome restrictions in measurement range as it offers precise results over an entire competition distance (e.g. 400m). Therefore it supports expanding opportunities to analyze human performance in field-based settings that may offer a considerable contribution to enhance the quality of training and lead to a deeper understanding of performance in track and field events.